Pengembangan Aplikasi Ma-Math Untuk Pengenalan Matematika Paud Berbasis Kearifan Lokal Kabupaten Ngawi - Kusumastuti, Narendradewi; Koesmadi, Dita Primashanti; Pangestu, Akhmadi Putro Aji; Kusuma, Wening Sekar; Ngaisah, Nur Cahyati (Universitas Muhammadiyah Metro, 2025)
This study aims to explain the need to develop applications for the introduction of PAUD mathematics based on local wisdom in Ngawi district, produce MA-MATH applications for the introduction of PAUD mathematics based on local wisdom in Ngawi district, test the effectiveness of the mamath application for the introduction of PAUD mathematics based on local wisdom in Ngawi district. This study uses research and development research that adapts the ADDIE development model of 5 main steps of development research, which include analysis, design, development, implementation and evaluation of media. The research subjects were children at Dharma Wanita Klitik I Kindergarten. The results of the study indicate that in the introduction of PAUD mathematics based on local wisdom requires the mamath application, the mamath application was developed from a product feasibility test carried out by 2 validators, namely the material validator and the validator with a very feasible category, the development of the MA-MATH application used has effectiveness in the introduction of PAUD mathematics because of significant differences in the introduction of PAUD mathematics based on local wisdom before and after using the